All-solid-state, long term stable, and embedded pH sensor for corrosion monitoring of concrete. (1st October 2022) - Du, Zhenxing; Wang, Penggang; Chen, Zhaoyi; Cui, Dongbo; Jin, Zuquan; Zhang, Hai
Abstract: The corrosion process of concrete usually accompanies pH changes of the pore solution. Thus, monitoring the pH value of concrete has great significance for the prediction of concrete corrosion. However, the most commonly used methods for measuring the pH value of concrete pore solution are destructive methods, which are very inefficient and cannot provide the pH value for real-time. In this study, an all-solid-state pH sensor constituted with iridium oxide (IrOx ) working electrode and manganese/manganese dioxide (Mn/MnO2 ) reference electrode was developed. The IrOx electrode fabricated with carbonate melt oxidation method and Mn/MnO2 fabricated with powder compaction method exhibited a dense and homogeneous micro structure. The as-prepared pH sensors showed remarkable long-term stability, ideal potential-pH response, low hysteresis, fast pH response time and strong resistance to ionic interference in solutions. Furthermore, the pH sensor was embedded in the mortar samples and used to monitor pH changes during the accelerated carbonation test. The results indicate that the pH sensor can provide accurate pH value variations of the mortar samples during the carbonation process, and it has great potential for non-destructively monitoring the corrosion process of concrete. Highlights: An all-solid-state pH sensor constituted with IrOx electrode and Mn/MnO2 electrode was developed. The performance of the pH sensor in solutions and cement mortar was investigated. The pH sensor exhibited remarkable precision for monitoring the carbonation process of mortar.